Castleman’s disease: A case report (Indian Journal of Case Reports, 2020)
Castleman’s disease (CD) is a rare non-malignant lymphoproliferative disorder of uncertain etiology. Its localized variety presents with incidentally found mass or symptomatic mass, whereas other type presents with generalized lymphadenopathy with systemic manifestations. Here, we report the case of localized CD in a 46-year-old female who presented with a complaint of vague upper abdominal pain for the past 6 months. The patient was managed with surgical resection only. Microscopic examination confirmed the entity to be CD of hyaline vascular type. The patient was asymptomatic at 15 months follow-up.